Knowledge, Attitude, and Behavior Level of Women of Reproductive Age toward Calcium Intake - Kartika Ratna Dewi; Eva M. Hidayat; Anita Rachmawati (Althea Medical Journal, 2018)
Background: Women have a higher risk of developing osteoporosis compared to men. Calcium intake is one of the determinant factor which can be modified to prevent osteoporosis. Knowledge, attitude and behaviour are important factors to fulfill the needs of calcium intake. This study aimed to describe  knowledge, attitude, and behavior toward calcium intake of woman of reproductive age.Methods: This descriptive study recruited 100 women (aged 20–30 years) in Jatinangor, West Java and was conducted from September to November 2014. Knowledge and attitude measurements used a validated questionnaire consisting of 10 and 9 closed questions respectively. Behavioral aspect was assessed using semi-quantitative Food Frequency Questionnaire (FFQ). Knowledge was classified as high, moderate, and low based on questionnaire scoring results, >75%, 60–75%, and <60% respectively. Attitude was categorized in two: positive and negative. Behaviour category used Recommended Dietary Allowances (RDA) as the cut-off point. If the  daily calcium intake is below the RDA it is categorized less and if the daily calcium intake equals to or exceeds the RDA it is categorized sufficient. The collected data were presented in frequency tabulation and percentage.Results: The majority of subjects  showed low to moderate level of knowledge toward calcium intake, 66% of subjects showed negative attitude towards calcium intake, and  98% showed calcium intake below the RDA. Conclusions: Subjects of this study have low to moderate level of knowledge, negative attitude toward calcium intake, and low level of behavior toward calcium intake.